1989
DOI: 10.1145/67450.67465
|View full text |Cite
|
Sign up to set email alerts
|

Some strategies of reuse in an object-oriented programming environment

Abstract: In a single-subject study of a software developer working in an object-oriented programming environment, we found evidence of a development style characterized by pervasive software reuse. The subject employed regular strategies for template selection and coding in her work, and avoided techniques requiring deep understanding of code details or symbolic execution whenever possible. Within the limits of the design of the study, the subject's performance is related to attributes of object-oriented programming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 3 publications
2
22
0
1
Order By: Relevance
“…It appeared that one particular element might be considered as a model at one moment and as a plugin component at another time. Our findings are consistent with results of previous studies on software design (Lange & Moher, 1989) or software enhancement by reusing supplied classes (Rosson & Carroll, 1993), and illustrate that models can also come from the current or other analogical problem domains.…”
Section: Interaction(s) Between Design and Reusesupporting
confidence: 91%
See 1 more Smart Citation
“…It appeared that one particular element might be considered as a model at one moment and as a plugin component at another time. Our findings are consistent with results of previous studies on software design (Lange & Moher, 1989) or software enhancement by reusing supplied classes (Rosson & Carroll, 1993), and illustrate that models can also come from the current or other analogical problem domains.…”
Section: Interaction(s) Between Design and Reusesupporting
confidence: 91%
“…Second, it examines reuse in the context of object-oriented programming which is assumed by its advocates to facilitate reuse. Few studies (Détienne, 1991;Lange & Moher, 1989) have analysed reuse in that context. 1 This research is partially sponsored by the European Esprit III SCALE 6334 project (System Composition and Large Grain Component Reuse Support) Our study focuses on the three following aspects of reuse : the interaction between design and reuse processes, the mental processes involved in reuse, and the mental representations constructed throughout the reuse activity.…”
Section: Framework and Goalsmentioning
confidence: 99%
“…Expert OO designers utilise reuse through built-in-classes whereas the novices do not spontaneously take advantage of built-in classes (Lee & Pennington, 1994). Second, contrary to the claims about how OO languages might facilitate reuse, Lange and Moher (1989) and Détienne (1991) found that reuse efforts did not centre on reuse by specialising the inheritance hierarchy but rather on literal copying and modification of code. Third, reuse involves some particular expertise different from expertise in the programming domain and expertise in the problem (task) domain.…”
Section: Reuse Activitymentioning
confidence: 98%
“…So, when developers encounter problems that have already been solved in the past, rather then re-inventing the wheel, or spending time componentizing the already available solution (which is sometimes not preferable [8]) they perform reuse tasks [2]. Reusing source code that was not designed in a reusable fashion is known by different synonyms: copyand-paste reuse [10], code scavenging [9] and, more recently, pragmatic-reuse [5]. Pragmatic reuse treats the system in a white-box fashion and involves extracting functionality from an existing system and reusing it within another system.…”
Section: Introductionmentioning
confidence: 99%